Trucking Travel App (2022)
The independent cargo transport service has problems in the search for travel offers, since there is no platform that it can use daily in the tasks that they need today and that are so weak. This weakness is due to the fact that the technological advance that we are facing in these times is not being taken advantage of. To solve this problem, this project explains the implementation of a mobile application made with the Android operating system, which is dynamic, easy to use and access. For its development, the Android Studio tool was used, which is a framework for the development of applications for Android devices. The mobile application is called TRUCKING TRAVEL whose purpose is to make it easier for the cargo carrier to easily search for their trip, thus reducing costs and time, online from a mobile device, whether smartphone, tablet, etc. This requirement can be done from the comfort of your home, office or anywhere the user is, whether transported or publisher, providing comfort, ease and without the need to take a long time to find the charging service. On the other hand, the application will have the notification service so that the carrier is updated on the offers that the publisher sent, in addition to a rating that can be given to each trip so that the carrier has a guide on how each publisher is. with his trip and thus be able to generate confidence within the guild. To conclude, the purpose of the project is to make life easier for the transporter, reduce costs and waiting time between each trip, give them the possibility that with a single click on their mobile device they can find their cargo.